PERAN PENGENDALIAN INTERNAL, INTEGRITAS, DAN PROFESIONALISME DALAM MENCEGAH KECURANGAN APARATUR SIPIL NEGARA PEMERINTAH PROVINSI RIAU: THE ROLE OF INTERNAL CONTROL, INTEGRITY, AND PROFESSIONALISM IN PREVENTING FRAUD IN THE STATE CIVIL APPARATUS OF THE GOVERNMENT OF RIAU PROVINCE - Kurniawan, Raja M.Mubyansa; Anugerah, Rita; Wiguna, Meilda (Universitas Riau, 2025)
There is a lot of fraud that harms an organization, especially the Regional Apparatus Organization (ASN). One form of fraud that often occurs is corruption, therefore fraud must be prevented through fraud prevention. The purpose of this study is to evaluate and assess how internal control, integrity, independence, and professionalism affect the prevention of fraud in the province of Riau regional apparatus organizations. 756 state government servants with positions in echelons 2, 3, and 4 in 46 Regional Apparatus Organizations (OPD) in the province of Riau made up the study's population. Purposive sampling was employed in the sampling procedure. 184 civil personnel with jobs in 46 OPDs made up the study's sample size. Multiple linear analysis techniques are used in the data processing procedure. The findings demonstrated that fraud prevention was impacted by internal control, honesty, independence, and professionalism in the Riau Province Regional Apparatus Organization. Based on the findings of this investigation in order to stop, steer clear of, and reduce fraud charges, leaders should be able to focus on the state of ASN related to Internal Control. Integrity, Independence, and Professionalism of ASN